Childbirth Was Never Meant to Be an Individual Project: Kusungirwa, Collective Care, and the Clinical Implications of Postpartum Depression Among Shona Women in Zimbabwe - Nomalanga Mahachi (International Journal of Recent Advances in Multidisciplinary Topics, 2026)
Postpartum depression (PPD) is estimated to affect one in three mothers in Zimbabwe, yet primary health care practitioners do not routinely screen for it, and culturally responsive clinical approaches are not used. Purpose: This paper explores the hypothesis that the Shona indigenous postpartum practice of "Kusungirwa,” where a new mother returns to her maternal home to receive structured care from female kin, is a community-based psychosocial intervention, and factors that protect against depression are directly translatable to contemporary psychological theory. This paper engages in a critical theory synthesis of Bowlby’s (1969) attachment theory and Berry's (1997) acculturation theory and a review of empirical and ethnographic literature on postpartum practices and PPD in Zimbabwe. Results/Discussion: The interpersonal, nutritional, and labour-saving components of "Kusungirwa" work to address the exact neurobiological and psychological factors that render postpartum women vulnerable to depression. Two recurrent clinical traps pathologising collective care and offering unstructured individual psychotherapy in the absence of support are explored and reframed in a cultural humility framework (Hook et al., 2013; Tervalon & Murray-García, 1998). Conclusions: Practice, community, and policy recommendations are provided, including culturally sensitive screening, engagement of traditional birth attendants in referrals, and the need for routine postpartum screening in Zimbabwean primary health care. The loss of "Kusungirwa” through urbanisation, economic hardship, and migration is not only cultural, but a tangible public mental health threat, and its deliberate recreation is a clinical and moral obligation.